Answer: 9
Step-by-step explanation:
2 - 8 = -6
3 - -6 = 9
Answer:
![\lim\limits_{(x,y)\rightarrow(0,0)}\left(\sqrt{-2x^2-6y^2+1}+1\right)=2](https://tex.z-dn.net/?f=%5Clim%5Climits_%7B%28x%2Cy%29%5Crightarrow%280%2C0%29%7D%5Cleft%28%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1%5Cright%29%3D2)
Step-by-step explanation:
We need to first simplify the expression using rationalization(i.e. if a square root term exists in the denominator, then multiply and divide the whole expression by the denominator(but the change the sign of its middle term))
here, we need to find:
![\lim\limits_{(x,y)\rightarrow(0,0)}\left(\dfrac{-2x^2-6y^2}{\sqrt{-2x^2-6y^2+1}-1}\right)](https://tex.z-dn.net/?f=%5Clim%5Climits_%7B%28x%2Cy%29%5Crightarrow%280%2C0%29%7D%5Cleft%28%5Cdfrac%7B-2x%5E2-6y%5E2%7D%7B%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D-1%7D%5Cright%29)
first we'll rationalize our expression:
![\dfrac{-2x^2-6y^2}{\sqrt{-2x^2-6y^2+1}-1}\left(\dfrac{\sqrt{-2x^2-6y^2+1}+1}{\sqrt{-2x^2-6y^2+1}+1}\right)](https://tex.z-dn.net/?f=%5Cdfrac%7B-2x%5E2-6y%5E2%7D%7B%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D-1%7D%5Cleft%28%5Cdfrac%7B%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1%7D%7B%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1%7D%5Cright%29)
![\dfrac{-(2x^2+6y^2)(\sqrt{-2x^2-6y^2+1}+1)}{(\sqrt{-2x^2-6y^2+1}+1)^2-(1)^2}](https://tex.z-dn.net/?f=%5Cdfrac%7B-%282x%5E2%2B6y%5E2%29%28%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1%29%7D%7B%28%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1%29%5E2-%281%29%5E2%7D)
![\dfrac{-(2x^2+6y^2)(\sqrt{-2x^2-6y^2+1}+1)}{-2x^2-6y^2+1-1}](https://tex.z-dn.net/?f=%5Cdfrac%7B-%282x%5E2%2B6y%5E2%29%28%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1%29%7D%7B-2x%5E2-6y%5E2%2B1-1%7D)
![\dfrac{-(2x^2+6y^2)(\sqrt{-2x^2-6y^2+1}+1)}{-(2x^2+6y^2)}](https://tex.z-dn.net/?f=%5Cdfrac%7B-%282x%5E2%2B6y%5E2%29%28%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1%29%7D%7B-%282x%5E2%2B6y%5E2%29%7D)
![\sqrt{-2x^2-6y^2+1}+1](https://tex.z-dn.net/?f=%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1)
this is our simplified expression, now we can apply our limits:
![\lim\limits_{(x,y)\rightarrow(0,0)}\left(\sqrt{-2x^2-6y^2+1}+1\right)](https://tex.z-dn.net/?f=%5Clim%5Climits_%7B%28x%2Cy%29%5Crightarrow%280%2C0%29%7D%5Cleft%28%5Csqrt%7B-2x%5E2-6y%5E2%2B1%7D%2B1%5Cright%29)
![\sqrt{-2(0)^2-6(0)^2+1}+1](https://tex.z-dn.net/?f=%5Csqrt%7B-2%280%29%5E2-6%280%29%5E2%2B1%7D%2B1)
![1+1](https://tex.z-dn.net/?f=1%2B1)
![2](https://tex.z-dn.net/?f=2)
the limit does exists and it is 2.
Answer:
y=1/2x+6
Step-by-step explanation:
Change to slope intercept form: y=1/2x-2
Take out the b term
Plug in point (-8, 2)
Get b as 6
Plug in b
Get y=1/2x+6
Answer:
7^8
Step-by-step explanation:
(7^2)^4
We know a^b^c = a^(b*c)
(7^2)^4 = 7^(2*4)
= 7^(8)